High-performance monoclinic WO3 nanospheres with the novel NH4+ diffusion behaviors for aqueous ammonium-ion batteries - Wen, Xiaoyu; Luo, Jinhua; Xiang, Kaixiong; Zhou, Wei; Zhang, Changfan; Chen, Han (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •The facile and controllable synthesis for monoclinic WO3 nanospheres.•The novel three-dimensional equilibrium diffusion behaviors for monoclinic WO3.•The continuous geometric evolutions of hydrogen bonds for monoclinic WO3.•WO3 revealed fast kinetics and durable stability for aqueous ammonium-ion batteries. Aqueous ammonium-ion batteries (AAIBs) have attracted tremendous attentions due to their plentiful resources, inherent security and environmental friendliness. From the first-principles calculations and ex-situ measurements, monoclinic WO3 revealed the three-dimensional equilibrium diffusion behaviors during the electrochemical processes, and the novel evolution processes of reversible building/breaking between geometric hydrogen bonds and traditional linear hydrogen bonds. Specifically, monoclinic WO3 delivered a high specific capacity of 150.6 mAh g-1 at the current density of 0.1 A g-1, and exhibited excellent rate capability of 48 mAh g-1 at the current density of 5.0 A g-1 and outstanding cycling stability of 86.6 % capacity retention after 500 cycles. Furthermore, the ammonium-ion full batteries based on the monoclinic WO3 anode and γ-MnO2 cathode achieved a perfect energy density of 64.9 Wh kg-1 and an extreme ultra-long lifespan with 95.4 % capacity retention after 5000 cycles at the current density of 3.0 A g-1. Thus, the novel insights on NH4+ diffusion behaviors and the evolution mechanisms of hydrogen bonds could promote the development of the practical applications for monoclinic WO3 in aqueous ammonium-ion batteries.